The Relevance of Word of Mouth Strategy in the Era of Modernization - Faturahman, Muhammad (Economics and Business International Conference Proceeding, 2024)
Using a literature review technique, this study seeks to determine the degree to which the word-of-mouth (WOM) strategy is relevant in dealing with the dynamics of the modernizing era. WOM is still one of the best marketing techniques for establishing credibility and swaying customer choices, even in the face of technology's quick advancement and shifting communication styles. This study examines a number of earlier research projects concerning the use and impact of word-of-mouth (WOM) in a completely digital setting and technological and social media modernization. This study clarifies the idea of word-of-mouth (WOM), its traits, and the evolution of its function in the context of digital communication through an extensive literature review. The study's findings demonstrate that WOM tactics are still effective when properly adjusted to new communication channels and technology. For WOM to be effective, however, issues including the pace of information, digital accessibility, and shifts in consumer behavior provide obstacles that need to be overcome. This study comes to the conclusion that WOM methods can be made more effective by having a better awareness of the features of modernization, technology, and social media environments. The study's implications also help marketing and business professionals create creative and adaptable communication strategies that will maximize the benefits of word-of-mouth (WOM) in fostering customer connections and increasing brand loyalty.